Incorporation of green solvent for low thermal budget flower-like Copper(I) Iodide (?-CuI) for high-efficiency solar cell - Aliyaselvam O.V.; Arith F.; Mustafa A.N.; Chelvanathan P.; Azam M.A.; Amin N. (Springer, 2024)
High conductivity, density, and uniform Copper(I) Iodide (CuI) as Hole Transporting Layer (HTL) was prepared directly on an Indium-doped Tin Oxide (ITO) substrate. A new green solvent, namely Monoethanolamine (MEA) with no additional additives procedures was presented for the preparation, though the fabricated CuI films produced a notable result of HTL for perovskite solar cell (PSC) applications. The growth of ?-CuI can be formed at the lower temperature of 350C, thereby lowering the fabrication cost since a high temperature involved fabrication method incurs large costs. The optimized annealing temperature of 80C has attained a pristine morphology structure with high conductivity of 28.38 S/cm. Besides, the SCAPS-1D simulation was used to construct an efficient CuI-based PSC using the experimental data collected of fabricated CuI films and attained a PCE of 21.37%, FF of 82.77%, J sc of 22.74mA/cm2 and V oc of 1.14V. Interestingly, this is the first report proposing the use of MEA as a CuI solvent, demonstrating the effective combination of solvent and annealing temperature can yield a desirable CuI structure. With that, HTL films can be prepared in simple, inexpensive, and rapid, thus reducing the cost of solar cell production. 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.